Characterization of genetic diversity and population structure within Staphylococcus chromogenes by multilocus sequence typing. - Rebeca Huebner; Robert Mugabi; Gabriella Hetesy; Lawrence Fox; Sarne De Vliegher; Anneleen De Visscher; John W Barlow; George Sensabaugh (PLoS ONE)
Staphylococcus chromogenes is a common skin commensal in cattle and has been identified as a frequent cause of bovine mastitis and intramammary infections. We have developed a seven locus Multilocus Sequence Typing (MLST) scheme for typing S. chromogenes. Sequence-based typing systems, such as MLST, have application in studies of genetic diversity, population structure, and epidemiology, including studies of strain variation as a factor in pathogenicity or host adaptation. The S. chromogenes scheme was tested on 120 isolates collected from three geographic locations, Vermont and Washington State in the United States and Belgium. A total of 46 sequence types (STs) were identified with most of the STs being location specific. The utility of the typing scheme is indicated by a discrimination power of 95.6% for all isolates and greater than 90% for isolates from each of the three locations. Phylogenetic analysis placed 39 of the 46 STs into single core group consistent with a common genetic lineage; the STs in this group differ by less than 0.5% at the nucleotide sequence level. Most of the diversification in this lineage group can be attributed to mutation; recombination plays a limited role. This lineage group includes two clusters of single nucleotide variants in starburst configurations indicative of recent clonal expansion; nearly 50% of the isolates sampled in this study are in these two clusters. The remaining seven STs were set apart from the core group by having alleles with highly variable sequences at one or more loci. Recombination had a higher impact than mutation in the diversification of these outlier STs. Alleles with hypervariable sequences were detected at five of the seven loci used in the MLST scheme; the average sequence distances between the hypervariable alleles and the common core alleles ranged from 12 to 34 nucleotides. The extent of these sequence differences suggests the hypervariable alleles may be remnants of an ancestral genotype.